PERSEPSI POLITIK PEMILIH KAUM DIFABEL (DIFFERENT ABILITY) TERHADAP PEMILIHAN UMUM WALIKOTA DAN WAKIL WALIKOTA SURAKARTA TAHUN 2015 - Rengga Nurrasyid; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2018)
In 2015, the executive and legislative goverment made dicision for the implementation of simultaneous elections which held for every region whom governor / mayor terms of service would complete by 2015. On 9th December 2015, the elections held, one of the region is Surakarta. Among every citizens who have voting rights in the elections, there are people with physical or mentally boundaries, people with different abilities. Regulation and condition had adjusted to ease diffable people who used their voting rights, but it was under expectation. The objective of this research was to find out diffable voter's political perception towards election in Surakarta by 2015. This research used Almond & Verba indicators to answered the problems in line with the purpose of the research, which is knowledge, participation, and assessment to election. Accessibilty was added too as additional indicator to find out the implementation of election.This research used quantitative and descriptive method which analyzed and presented in tabular formed, processed by SPSS program to generate valid results. Population for this research was all diffable voters in Surakarta, and 54 samples taken by stratified random sampling technique. The result showed that most of diffable voter's political perception was in good level, they have searched for the information and participated the election. In order to make the election will be accessible for diffable voters, goverment shall increase the  service and capacity of the facilities and infrastructures that suitable for their needs.  Keywords: Election; Perceptions of Different Voters; Access Election